DEVELOPMENT & OPTIMIZATION OF ALLYL AMINE ANTIFUNGAL NANOEMULGEL USING 23 FACTORIAL DESIGN: FOR THE TREATMENT OF TINEA PEDIS - Syamala, UrmilaSri (European Scientific Journal, ESJ, 2014)
Drug permeation through skin from topical nanoemulsion (NE) depends on the concentration of the oil phase, aqueous phase, surfactant and co surfactant. Hence it is very important in optimizing the composition of NE. The conventional method of experimentation is costlier and is restricted to changing one factor at a time, the other factors being kept constant. Hence, there is a need of design of experiment (DoE), a statistical tool for finding optimum combination, using relationship between factors affecting a process and output of that process. The levels of the critical factors influencing the NE formation, were obtained from pseudo ternary phase diagram. From the design matrix of DoE, formulation matrix was generated which were analyzed for globule size as response. The model was found to be highly significant from the F ratio (71.49) and R2 value of 0.9940. The optimized formulation was found to pass the stability and viscosity test (approx.120 cP). Ex-vivo skin permeation test of nanoemulgel (NG) formulation showed skin permeability of approximately 20% of the drug, while the marketed cream (MC) showed a permeability of 18% only. The amount of drug retained in the skin by the NG formulation was found to be approximately 31% while for the MC it was found to be only 20%. The NG formulation was found to treat the infected rat skin within 12 days of treatment while the MC took about 16 days for complete removal of the infection. Thus the NG formulation effectively permeates to the layers of the skin and treats the fungal infection more effiently than the MC.